2022
DOI: 10.3390/ma15041429
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Random Plasmonic Metasurfaces on Fluorescence Enhancement

Abstract: One of the strategies employed to increase the sensitivity of the fluorescence-based biosensors is to deposit chromophores on plasmonic metasurfaces which are periodic arrays of resonating nano-antennas that allow the control of the electromagnetic field leading to fluorescence enhancement. While artificially engineered metasurfaces realized by micro/nano-fabrication techniques lead to a precise tailoring of the excitation field and resonant cavity properties, the technological overhead, small areas, and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…It facilitates the study of random distributions of metallic NPs which are promising inexpensive platforms. Indeed, Anăstăsoaie et al have recently shown that biosensors based on random plasmonic metasurfaces can have a fluorescence enhancement factor comparable to that which artificially engineered metasurfaces realized by micro- and nanofabrication techniques achieve. Random patterns of plasmonic NPs are also a good approach to produce optical physically unclonable functions (O-PUFs) .…”
Section: Discussionmentioning
confidence: 99%
“…It facilitates the study of random distributions of metallic NPs which are promising inexpensive platforms. Indeed, Anăstăsoaie et al have recently shown that biosensors based on random plasmonic metasurfaces can have a fluorescence enhancement factor comparable to that which artificially engineered metasurfaces realized by micro- and nanofabrication techniques achieve. Random patterns of plasmonic NPs are also a good approach to produce optical physically unclonable functions (O-PUFs) .…”
Section: Discussionmentioning
confidence: 99%